ANALYSIS OF PRODUCTION COSTS AND INCOME OF OYSTER MUSHROOM (Pleurotus ostreatus) BAGLOG - Siska Yulianita Lubis; Faisal Azhari Baldan Panjaitan; Nurhayati; Shampazuraini Samsuri (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
The purpose of this study was to calculate the production costs of oyster mushroom baglogs and the income of oyster mushroom baglog businesses in Deli Serdang. This study was conducted in Deli Serdang from March to June 2023. This study used a purposive sampling method. The data for this study were taken through observation and interviews with respondents who were oyster mushroom baglog farmers. Analysis of production cost data, amount of income and income results are: production costs incurred by oyster mushroom baglog farmers amounting to IDR 5,266,109, income of IDR 9,900,000 and income of IDR 4,633,109